Identifikasi Karakter Morfologi Tanaman Ubi Kayu (Manihot esculenta Crantz) di Kecamatan Leihitu, Kabupaten Maluku Tengah - Patty, Jacob R; Polnaya, Fransin; Lesilolo, Marthini K (Fakultas Pertanian, Universitas Pattimura, 2025)
Indonesia has traditionally grown cassava (Manihot esculenta Crantz), a member of the Euphorbiaceae family, as a major food crop. Morphological changes in size, shape, color, and yield are the result of adaptation processes. The goal of Indonesia's cassava breeding program is to create sweet and bitter varieties that are high yielding, disease and pest-tolerant, have restricted branching, have good tuber form, are able to adapt to different soil and climate conditions, and mature at the right time. The purpose of this study was to determine the morphological traits of the cassava varieties found in Central Maluku Regency's Leihitu District. Descriptive analysis was used to perform research in eight villages: Morella, Mamala, Hitu Meseng, Hitu Lama, Wakal, Hila, Kaitetu, and Seith. English cassava, Bisstein cassava, Karas (Bitter) cassava, Porridge (Lombo) cassava, Sukabumi cassava, Kapok cassava, and Mantega cassava were the eight types named. Whereas Morella and Mamala Villages had the least amount of varietal variation, Kaitetu Village had the most. Significant morphological variety among cassava varieties in Leihitu District was indicated by dendrogram analysis, which showed two to seven groups at kinship distance scales of 5 to 25.